Impact of a simple educational intervention on awareness regarding cardiovascular disease among school-going adolescents in a rural area of Bengaluru district, India - Vivek Bhat; Reubel Coates; Deepthi Shanbhag; Natasha Pillai; Neha Zacharias; Reema D'Souza; Geo Judes Mathew (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Cardiovascular disease (CVD) is the number one cause of death in India. Atherosclerosis begins in the second decade of life; thus, preventive efforts beginning in adolescence are crucial. Yet, there are no national or regional school-based educational programs in India for the prevention of CVD. We aimed to assess the impact of a simple educational intervention on the awareness regarding CVD among school-going adolescents in a rural area of Bengaluru. MATERIALS AND METHODS: This study was conducted using a convenience sample of school-going adolescents of classes 8, 9, and 10 in three schools in a rural area of Anekal subdistrict, Bengaluru, with a sample size of 170. A standardized, validated questionnaire testing CVD awareness was administered, followed by a simple lecture with audio-visual aids on key aspects of CVD. Three weeks later, the same questionnaire was administered to the same students. The results were then analyzed using appropriate descriptive (mean, percentage) and inferential analyses (Chi-square, paired t-test). RESULTS: The mean (SD) age was 14.5 (1.0) years, and 54% (n = 100) were boys. 75% (139) belonged to privately funded schools. 23% (43) belonged to class 8, 37% (69) to class 9, and 40% (74) to class 10. The mean (SD) total score on baseline assessment was 27.4 (9.3) out of 100, with girls and students of private schools scoring higher. The mean (SD) post-test total score was 48.5 (15.7), with significant increases in all domains of awareness, and in all categories of students. DISCUSSION: Awareness regarding CVD among adolescents from rural Bengaluru was poor, highlighting the need for educational interventions to aid preventive efforts. A simple educational intervention resulted in significant improvements in CVD awareness, even after 3 weeks.